18 'Tell me what's happened': when linguistic choices affect efficiency of ambulance dispatch for cardiac arrest. (21st May 2017) - Riou, M; Whiteside, A; Ball, S; Williams, T; O'Halloran, KL; Perkins, GD; Bray, J; Cameron, P; Smith, K; Fatovich, DM; Inoue, M; Brink, D; et al.
Abstract : Aim: Clear and efficient communication between emergency caller and call-taker is crucial to timely ambulance dispatch. Within the Medical Priority Dispatch System, 1 the first opportunity that callers have of describing the situation is after the scripted prompt "okay, tell me exactly what happened". However, in 60% cases, call-takers introduce a slight linguistic variation (what's happened v. what happened). This study analyses the effect of this change on the way callers describe the emergency. Methods: Using a mixed-methods analysis combining Conversation Analysis and Corpus Linguistics, we analysed 184 calls from paramedic-confirmed out-of-hospital cardiac arrests in Perth (Western Australia) in 2014–2015. We coded each call for its use of tense in the prompt and the format of the response as either a report (focusing on symptoms) or a narrative 2 (containing irrelevant background details) and we timed the callers' responses. Results: The use of report response was much more frequent when call-takers chose the present perfect (what's happened) rather than the simple past (what happened) (72% v. 43%, p<0.0001). We found that the median length of caller response was significantly shorter when it was structured as a report rather than a narrative (9 v. 18 s, p<0.0001). Reports unfolded more efficiently over a median of 3 turns (v. 6 for narratives, p<0.0001). Conclusion: A change of tense can impact how efficiently callers describe a time-critical emergency. Our results suggest that a better understanding of linguistic and interactional dynamics can improve dispatch performance. References: Medical Priority Dispatch System (version 12.1.3). Salt Lake City, Utah, USA: Priority Dispatch Corp. Labov W, Waletzky J. Narrative analysis: Oral sessions of personal experience. In: Helm J, editor. Essays Verbal Vis. Arts, Seattle: University of Washington Press; 2003, p. 74–104. Conflict of interest: A. Whiteside and D. Brink receive full salary support, and P. Bailey, M. Inoue and J. Finn receive partial salary support from St John Ambulance. Funding: Funding for this research was received from an Australian NHMRC (National Health and Medical Research Centre) Partnership Project: #1076949 'Improving ambulance dispatch to time-critical emergencies'. J. Finn and J. Bray receive partial salary support from the NHMRC 'Aus-ROC' Centre for Research Excellence #1029983. J. Bray receives salary support from an NHMRC/NHF (National Heart Foundation) Early Career Fellowship.